Studi Inhibitor Korosi Berbasis Imidazoline Salt Pada Brine Water Di Pipa Penyalur Minyak Mentah [Studies of Imidazoline Salt Inhibitor for Brine Water in Crude Oil Pipeline] - Lutviasari Nuraini; Gadang Priyotomo; Ronald Nasoetion; Harsisto Harsisto (National Research and Innovation Agency (BRIN), 2016)
A study of imidazoline salt inhibitor for brine water in crude oil pipeline was carried out using tafel polarization test, Fourier Transform Infrared Spectroscopy (FTIR) and Electrochemical Impedance Spectroscopy (EIS). A type of specimen used in this research is API 5L grade B. The solution of brine water came from fluid in crude oil pipeline. The addition of commercial inhibitor of imidazoline salt base was conducted with range of 3-40 ppm for polarization test and range of 3-20 ppm for EIS test. The addition of imidazoline salt at 3-20 ppm is effective to decrease corrosion rate and to increase inhibitor efficiency up to 95% . The resistance of adsorbed molecule layer increase with the addition of inhibitor compared without inhibitor, where this addition could decrease the electrochemical reaction on the surface. The decrease of corrosion rate took place due to the presence of adsorbed thin layer in metal surface.AbstrakStudi kinerja inhibitor imidazoline salt pada brine water di pipa penyalur minyak mentah dilakukandengan melakukan pengujian tafel, Fourier Transform Infrared Spectroscopy (FTIR) dan Electrochemical Impedance Spectroscopy (EIS). Jenis spesimen uji baja yang digunakan dalam penelitian adalah API 5L dan larutan brine water berasal dari 70% dari total fluida di pipa penyalur minyak mentah. Penambahan inhibitor komersial berbasis imidazoline salt dilakukan dengan variasi 3 - 40 ppm untuk pengujian polarisasi dan variasi 3 - 20 ppm untuk pengujian EIS. Penambahan inhibitor berbasis imidazoline salt antara 3 – 20 ppm secara efektif dapat menurunkan nilai laju korosi dan meningkatkan efisiensi inhibitor hingga 95%. Tahanan lapisan adsorpsi molekul dengan penambahan inhibitor meningkat dibandingkan kondisi tanpa inhibitor, dimana hal ini dapat menurunkan aktifitas reaksi elektrokimia di permukaan baja. Penurunan laju korosi terjadi dikarenakan pembentukan lapisan tipis yang teradsopsi di permukaan logam.